An investigation into whether young teens change their clothing consumer behaviour and brand preferences after the transition from primary school (grade seven) to high school (grade eight) in the South Western Cape - Fischer, Carolyn (School of Management Studies, 2015)
Includes bibliographical references (leaves 149-159).